Evaluation Efficacy Of Some Oils Plant Against Of Callosobruchus maculatus (Fabricius) (Coleoptera: Bruchidae) - Qays Assi Ahmade Salh Al-Daoodi; Burhan M. M. AL-dulemiy (Tikrit Journal of Pure Science, 2023)
This study was conducted to know the impact of treatment of cowpea seeds plant oils as following: - Black seed, castor, sunflower, Alsi and Brassica on Southern cowpea weevil C. maculatus at concentration of (1.5, 3, 4.5) ml / kg seeds. The study showed superiority of mustard oil in reducing the average of number of eggs laid on the seeds as it reached 161.13 while the highest rate reached to 208.25 when the testing seeds treatment with sunflower oil. The study also showed that the longer period for exit of the members of the first generation (F1) 28.08 day when the seed treated with mustard oil, while minimum period of 27.00 days when treated with castor oil seeds. We see that the lowest rate for a number of emerging insects 48.50 at the treatment of linseed oil, while the highest rate for a number of emerging insects 53.50 at the treatment of black seed oil. It was found that the lowest rate of damage was 24.90% with linseed seed oil and the highest rate was 29.73 with black seed oil, While the highest rate was in seed weight 21.60% with black seed oil and the lowest rate was 16.88% with mustard oil, And the treatment of the seeds of cowpea plant oils which was used in this study did not show adverse effects on the vital seed treatment significantly. As the results showed that the amount of oil is inversely proportional to both the number of eggs and emerging insects and the percentage of damage, loss and germination, and directly proportional to the period of time required for the exit of members of the first generation (F1).